2021
DOI: 10.1371/journal.pone.0252032
|View full text |Cite
|
Sign up to set email alerts
|

Bioturbation by black soldier fly larvae—Rapid soil formation with burial of ceramic artifacts

Abstract: Bioturbation involves the incorporation of residues from the surface soil into the subsoil; however, common small soil ‘bioengineers’, such as earthworms or termites, are unlikely to transport human artifacts to deeper soil horizons. However, such artifacts occur in the deeper soil horizons within Amazonian Anthrosols (Terra Preta). Here we test the assumption that such tasks could be carried out by fly larvae, which could thus play a crucial role in waste decomposition and associated soil mixing under tropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…However, recent studies have reported significantly higher carbon dioxide emissions from soils amended with BSFFF compared to conventional compost and unfertilized soil, due to increase in basal respiration ( Fuhrmann et al, 2022 ); this warrants further research to generate accurate conclusions on the influence of ICOF on soil greenhouse emissions. Nevertheless, bioturbation activities of BSF larvae have been found beneficial in incorporating soil organic matter and increasing soil volume ( Orozco-Ortiz et al, 2021 ). Moreover, insect frass has been found beneficial in accelerating litter decomposition, soil organic matter transformation, and enzymatic activities, and regulating nutrient cycling in natural ecosystems, which are critical for maintaining the soil food web and ecosystem balance ( Hwang et al, 2022 ; Madritch et al, 2007 ).…”
Section: Benefits Of Insect-composted Organic Fertilizers On Soil Qua...mentioning
confidence: 99%
“…However, recent studies have reported significantly higher carbon dioxide emissions from soils amended with BSFFF compared to conventional compost and unfertilized soil, due to increase in basal respiration ( Fuhrmann et al, 2022 ); this warrants further research to generate accurate conclusions on the influence of ICOF on soil greenhouse emissions. Nevertheless, bioturbation activities of BSF larvae have been found beneficial in incorporating soil organic matter and increasing soil volume ( Orozco-Ortiz et al, 2021 ). Moreover, insect frass has been found beneficial in accelerating litter decomposition, soil organic matter transformation, and enzymatic activities, and regulating nutrient cycling in natural ecosystems, which are critical for maintaining the soil food web and ecosystem balance ( Hwang et al, 2022 ; Madritch et al, 2007 ).…”
Section: Benefits Of Insect-composted Organic Fertilizers On Soil Qua...mentioning
confidence: 99%